THE INFLUENCE OF POCKET MONEY AND LIFESTYLE ON THE INTEREST IN SAVING FOR STUDENTS OF THE FACULTY OF ISLAMIC ECONOMICS AND BUSINESS IAIN KERINCI - Yuliandari, Piari; Syukrawati, Syukrawati; Tiara, Tiara (Asian Journal of Islamic Economic Studies, 2024)
This study aims to determine the effect of Pocket Money and Lifestyle both simultaneously and partially on the interest in saving for students of the Faculty of Economics and Islamic Business IAIN Kerinci. This type of research is descriptive quantitative research. The population in this study is Febi IAIN Kerinci students majoring in Sharia Banking. The sample was determined using purposive sampling techniques, so that the respondents of this study amounted to 77 students. Data were collected using questionnaires. As for the data analysis technique using multiple linear regression analysis with the help of the SPSS program version 23. The results showed that both partially and simultaneously pocket money and lifestyle had a significant effect on the interest in saving for students of the Faculty of Economics and Islamic Business IAIN Kerinci. Keywords: Lifestyle; Interest in Saving; Student Pocket Money